AN INFLUENCE OF SOSIAL MEDIA AND SERVICE QUALITY PRODUCT PURCHASE DECISIONS AT E-COMMERCE SHOPEE - Nabila Yudisha; Indra Gunawan; Herdi Gunawan; Margie Subahagia Ningsih; Sari Novalianda (Jurnal Scientia, 2023)
This study aims to determine how much influence social media and service quality have on product purchasing decisions at E-Commerce Shopee. The independent variables are social media and service quality and the dependent variable is purchasing decisions. The sampling technique used in this study was a purposive sampling technique with a sample of 97 respondents. Data collection techniques using questionnaires, documentation, observation and interviews. The research method used is quantitative method, this study uses primary data and secondary data with multiple linear regression models. Data processing was carried out using SPSS 26.0 software. Through the R test, social media and service quality have a strong relationship with purchasing decisions. The effect of social media and service quality on purchasing decisions is 68.9% and the remaining 31.1% is influenced by other factors not examined in this study. Partially seen from the t test, there is an influence of social media on purchasing decisions at E-Commerce Shopee and there is an influence of service quality on purchasing decisions at E-Commerce Shopee.